A Semiotic Analysis of Sophie's Identity in The School for Good and Evil (2022) Film - Hasana Putri Prasetyana; Titis Setyabudi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aimed to examine how Sophie's identity is conveyed through signs (icon, index, and symbol) in the film The School for Good and Evil. The type of this study is qualitative research and uses descriptive research design. The data consists of visual and verbal signs. The data were collected by repeatedly watching the film, selecting key scenes, documenting relevant visuals, coding them according to Peirce's semiotic consisting of triadic model and types of signs, and validating interpretations through secondary references. The data analysis employed Peirce's semiotic framework and Erikson's psychological development concept, which integrated with stages of data reduction, data display, and conclusion drawing. The analysis shows that icons depict Sophie's unstable self-perception, while indexes reveal the connection between her inner conflicts and external effects that indicate her identity confusion, and symbols depict the social and cultural expectations around her. These signs collectively illustrate Sophie's struggle between her authentic self and the identity imposed by external pressures. By uncovering how the film's semiotic elements guide the interpretation of identity conflict, this study highlights the role of cinema in constructing and influencing perceptions of self-worth, beauty, and morality in media narratives.